(419) The role and organization of the employment service in a developing economy. دور وتنظيم خدمة التوظيف في اقتصاد نامٍ. (The institute of national planning., 2018)
This study examines the role of employment services as one of the essential institutional components supporting economic development in developing countries. It focuses on the organizational and administrative structures required to improve labor market efficiency and ensure the effective utilization of human resources. The study is based on the assumption that economic development depends not only on investment and production growth but also on the existence of institutions capable of organizing labor market activities and coordinating available manpower resources with employment opportunities. The study begins by defining employment services as institutions responsible for collecting labor market information, identifying employment opportunities, and linking job seekers with productive and service sectors. It emphasizes the significance of such services in reducing labor market imbalances, particularly in developing economies characterized by unemployment, labor market imperfections, and limited manpower data systems. The paper further discusses the multiple functions performed by employment service institutions, including labor market information collection and analysis, vocational guidance, labor allocation, and support for employment and training policies. It argues that these services serve as important mechanisms for balancing labor supply and demand and reducing structural bottlenecks that may constrain economic growth. The study also examines organizational aspects related to employment service administration, emphasizing the importance of coordination among governmental agencies, educational institutions, training organizations, and productive sectors. It further highlights the need for efficient administrative and information systems that improve forecasting capabilities related to future labor market requirements. The academic significance of the research lies in its development of an analytical framework linking labor market policies with economic development objectives. Consequently, the study provides useful insights for researchers and policy makers interested in employment planning and labor market development strategies in developing economies.